Role of Calcium-Sensing Receptor in Mechanotransducer-Channel-Mediated Ca2+ Influx in Hair Cells of Zebrafish Larvae - Lin, Li-Yih; Yeh, Ya-Hsin; Hung, Giun-Yi; Lin, Chia-Hao; Hwang, Pung-Pung; Horng, Jiun-Lin (Frontiers in Physiology, 2018)
The calcium-sensing receptor (CaSR) is an extracellular Ca2+ sensor that plays a critical role in maintaining Ca2+ homeostasis in several organs, including the parathyroid gland and kidneys. In this study, through in situ hybridization, the expression of CaSR mRNA was found in the neuromasts of zebrafish larvae. Immunohistochemistry further demonstrated that the CaSR protein was present in neuromast hair cell stereocilia and basolateral membranes. Based on the expression and subcellular localization of the CaSR in hair cells, we hypothesized that the CaSR is expressed in zebrafish lateral-line hair cells to regulate mechanotransducer (MET)-channel-mediated Ca2+ entry. Using the scanning ion-selective electrode technique, MET-channel-mediated Ca2+ influx at the stereocilia of hair cells was measured in intact larvae. Ca2+ influx was suppressed after larvae were pretreated with a CaSR activator (R-568) or high-Ca2+ (HCa) medium. Gene knockdown by using morpholino oligonucleotides decreased CaSR expression in hair cells and eliminated the effects of R-568 and HCa on Ca2+ influx. In addition, we found that treatment with R-568 attenuated neomycin-induced hair cell death. This study is the first to demonstrate that the CaSR is involved in mechanotransduction in zebrafish hair cells.